2010
DOI: 10.1164/rccm.201002-0310oc
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacterial Lung Disease Prevalence at Four Integrated Health Care Delivery Systems

Abstract: Rationale: Single-site clinic-based studies suggest an increasing prevalence of pulmonary nontuberculous mycobacteria (NTM) disease, but systematic data are lacking. Objectives: To describe prevalence and trends for NTM lung disease at four geographically diverse integrated heath care delivery systems in the United States. Methods: We abstracted mycobacterial culture results from electronic laboratory databases and linked to other datasets containing clinical and demographic information. Possible cases were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
397
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 499 publications
(441 citation statements)
references
References 23 publications
24
397
3
12
Order By: Relevance
“…One third of the NTM patients in this study population were infected with M. kansasii , a proportion substantially higher than that seen in the United States ( 5 , 19 )and in other areas of Brazil ( 10 , 14 ) and Australia ( 20 ). Global geographic variability in M. kansasii has been noted; a high prevalence of M. kansasii lung disease occurs in Western Europe, Switzerland, and the United Kingdom ( 17 , 21 23 ).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…One third of the NTM patients in this study population were infected with M. kansasii , a proportion substantially higher than that seen in the United States ( 5 , 19 )and in other areas of Brazil ( 10 , 14 ) and Australia ( 20 ). Global geographic variability in M. kansasii has been noted; a high prevalence of M. kansasii lung disease occurs in Western Europe, Switzerland, and the United Kingdom ( 17 , 21 23 ).…”
Section: Discussionmentioning
confidence: 61%
“…Although we were unable to determine the true prevalence of disease caused by these organisms in the state of Rio de Janeiro, the current study confirmed an increasing frequency of patients referred with NTM lung disease. In some industrialized countries, the prevalence of NTM has been found to be increasing ( 5 , 17 ), although it remains unclear whether this increase is related to increasing awareness of physicians that leads to more frequent diagnosis, to improved laboratory capacity, or to a combination of both factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, PPV of stricter microbiologic criteria was considerably higher when compared to ATS/IDSA microbiologic criteria (93.3% vs. 59.8%). 4,17,18 Thus, to prevent unwarranted diagnoses and treatment of NTM disease, as well as unnecessary diagnostic delay, it could be helpful to use separate, more stringent criteria for species of low relevance, and less stringent criteria for species considered to be of high clinical relevance in the local setting. This aspect should be covered in the upcoming diagnostic criteria.…”
Section: Criteria Correlationmentioning
confidence: 99%